Advocate and Corruption Eradication - Erman Rajagukguk (Fakultas Hukum Universitas Islam Indonesia, 2008)
The role of advocate is of significant importance in the corruption eradication, especially in the side of litigation process. During litigation process, there is ethical dilemma experienced by such advocate in accomplishing advocacy on behalf of client. In such situation, the courage of an advocate in holding up the Advocate Ethical Code is very demanding. The meaning of corruption, in more sense, includes the abuse of power or position to enrich him/her self or others, the bribery and money laundering. An advocate is also possible for both a means of corruption device and a person eradiating corruption. These following paragraphs are to explain how an advocate enables to eradicate corruption in a three-activity way as he or she is responsible for in their daily activities: legal consultant, litigation and money laundering.